Variability in alluvial river width driven by intermittent bank collapse - Kun Zhao; Stefano Lanzoni; Giovanni Coco; Fan Xu; Kaili Zhang; Zheng Gong (Proceedings of the National Academy of Sciences, 2026)
Alluvial rivers have long been described by hydraulic geometry theory, which links equilibrium channel dimensions to flow discharge. Yet natural rivers are inherently dynamic, with planforms evolving over time and widths fluctuating around an equilibrium state. Despite increasingly refined datasets, the mechanisms underlying river width variability remain poorly understood. Here, we analyze a globally distributed set of alluvial rivers using high-resolution satellite imagery to examine spatial patterns of width variability. When normalized by mean channel width, we identify three characteristic wavelengths of width variability, each associated with a distinct geomorphic feature: meander bends, mid-channel bars, and localized bank-line incisions linked to intermittent bank collapse. Fourier analysis reveals a strong inverse relation between intermittent collapse-driven width variability and bend-average curvature, suggesting that intermittent bank collapse plays a prominent geomorphic role in mildly curved rivers. Numerical modeling further demonstrates that intermittent bank collapse affects the overall river morphodynamics, accelerating lateral migration and enhancing floodplain reworking. By illustrating intermittent bank collapse as a significant mechanism of river width adjustment, our findings refine classical fluvial geomorphology theory and hold implications for river restoration and organic carbon flux estimation in a warming era.